Peran dan Penerapan Akuntansi Perpajakan terhadap UMKM E-Commerce - Ali Hardana; Tongku Imam Raja Junjungan; Ali Wardani; Anwar Ibrahim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In Indonesia., Micro, Small and Medium Enterprises (MSMEs) have an important role in the community's economy. With the business trend in society over the last 5 years, namely e-commerce business, now more and more business people are running e-commerce MSMEs. The number of MSMEs should be comparable with the large amount of taxes received from the MSME sector, but in relity it is stated by the Directora.e General of Taxes (DJP) that MSMEs ha.ve not contributed optimally to tax revenues. The success of this tax revenue effort is determined by several interrelated things, namely the ability of MSMEs to manage business finances which of course adequate implementation of MSME accounting is required. The aim of this research is to test the effect of implementing MSME accounting on taxpayer compliance for e-commerce MSMEs by adding understanding of taxation, taxpayer awareness, and ease of access as control variables. This research uses a questionnaire technique. The sample used was 90 respondents using the convenience sa.mpling method. The analysis technique used in this research is Multiple Regression Analysis. The results shown by this research are that the implementation of MSME accounting has a positive effect on e-commerce MSME Taxpayer compliance. Meanwhile, the control variables that influence are understanding taxation and ease of access. Taxpayer awareness variables are not proven to be control variables in this research.